Effects of microbial diversity and phospholipids on flavor profile of caviar from hybrid sturgeon (Huso dauricus × Acipenser schrencki). (30th May 2022) - Xu, Xinxing; Lu, Shixue; Li, Xuefei; Bai, Fan; Wang, Jinlin; Zhou, Xiaodong; Gao, Ruichang; Zeng, Mingyong; Zhao, Yuanhui
Highlights: Key odorants in sturgeon caviar were identified. The uncultured and cultured microbial communities were ascertained. Non-volatile metabolites were profiled using metabonomics. Microbial communities and phospholipids were correlated with odorants. Abstract: Thirty-seven volatiles were identified by gas chromatography-ion mobility spectrometry in sturgeon caviar. Alkenes (37, 43), alcohols (30, 36), aldehydes (9, 10), and esters (11, 13) were detected by two-dimensional gas chromatography–time-off-flight mass spectrometry in fresh and stored caviar, respectively. Alkenes (humulene, caryophyllene, longifolene, and d -limonene), aldehydes (heptanal, hexanal, pentanal, and 3-methyl butanal), and 2-ethyl-1-hexanol were sniffed and described as providing fresh, fatty, and fishy attributes by gas chromatography-olfactometry. The fungal genera of Apiotrichum, Penicillium, Filobasidium, Gibberella, and Cladosporium and 16 bacterial genera were significantly correlated with variations in the contents of 25 aldehydes and 11 ketones. Nine strains, 20 fatty acids, and 69 differential phospholipids were isolated and profiled. Glycerophosphoethanolamine (20:2/20:4), glycerophosphoethanolamine (22:6/22:5), and glycerophosphocholine (16:0/13:0) were significantly associated with the formation of odorants and the proposed mechanism of flavor formation from phospholipids is summarized. This study represents a foundation for achieving targeted preservation and flavor control of caviar.